2019
DOI: 10.1371/journal.pbio.3000157
|View full text |Cite
|
Sign up to set email alerts
|

Multiple functional neurosteroid binding sites on GABAA receptors

Abstract: Neurosteroids are endogenous modulators of neuronal excitability and nervous system development and are being developed as anesthetic agents and treatments for psychiatric diseases. While gamma amino-butyric acid Type A (GABAA) receptors are the primary molecular targets of neurosteroid action, the structural details of neurosteroid binding to these proteins remain ill defined. We synthesized neurosteroid analogue photolabeling reagents in which the photolabeling groups were placed at three positions around th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
112
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 67 publications
4
112
0
1
Order By: Relevance
“…We did not test the effects of mutations on KK150 action because it minimally enhances [ 3 H]muscimol 3 binding. However, KK150 binds to all three of the identified NS binding sites, and may thus be a weak through all three sites but predominantly through the intersubunit and α1 intrasubunit sites, which we have 12 previously shown mediate PAM-NS potentiation (11). In contrast, 3β5αP and KK148 enhance…”
mentioning
confidence: 72%
See 4 more Smart Citations
“…We did not test the effects of mutations on KK150 action because it minimally enhances [ 3 H]muscimol 3 binding. However, KK150 binds to all three of the identified NS binding sites, and may thus be a weak through all three sites but predominantly through the intersubunit and α1 intrasubunit sites, which we have 12 previously shown mediate PAM-NS potentiation (11). In contrast, 3β5αP and KK148 enhance…”
mentioning
confidence: 72%
“…We have also shown that KK123 labeling of the α1 intrasubunit (α1Y415) and β3 intrasubunit (β3Y442) 3 sites ( Figure 5A) can be prevented by a ten-fold excess of 3α5αP (11). We thus examined whether 3β5αP 4 (30 μM) inhibited photolabeling by KK123 (3 μM).…”
mentioning
confidence: 94%
See 3 more Smart Citations